Oxygen-rich microporous carbons with exceptional hydrogen storage capacity - Troy Scott Blankenship II (Nature Portfolio, 2017)
Hydrogen is attractive as a clean fuel for motor vehicles and porous carbons represent promising hydrogen storage materials. Here, Mokaya and colleagues incorporate oxygen-rich functional groups into porous carbons with high microporosity, showing that such materials exhibit significantly enhanced H2 storage capacity.